PERTUMBUHAN IKAN ARWANA IRIAN (Scleropages jardinii Saville-Kent) DI AKUARIUM [Growth of Bonytongue Fish {Scleropages jardinii Saville-Kent) in Aquarium] - Agus H. Tjakrawidjaja (Jurnal Iktiologi Indonesia, 2006)
The aim of this research was to know growth in various life stages of Scleropagus jardinii Saville-Kent 1892 during domestication particularly the ranching system. Growth, food conversion, survival rate and water qualities were determined for each life stage. The result showed that each life stage is characterized by different growth. Highest food conversion was showed by adult followed by adolescent and juvenile have lowest amount of food conversion. Each life stage showed 100% for survival rate. Water quality in this experiment was adequate to support growth in fish.